Soluble epoxide hydrolase in the human placenta throughout gestation - Tai-Ho Hung; Szu-Fu Chen; T'sang-T'ang Hsieh (Elsevier, 2019)
Objective: To investigate the spatial and temporal changes of soluble epoxide hydrolase (sEH) in the human placenta throughout gestation and to study the effects of hypoxia-reoxygenation (HR) on the expression of sEH in villous explants in vitro. Materials and methods: Placental samples were obtained from women of different gestation and grouped as early (8-12 weeks, n = 10), mid- (16-28 weeks, n = 6), and late gestation (38-39 weeks, n = 10) according to gestational age. Immunohistochemistry, western blot, and real-time quantitative PCR were used to assess the cellular distribution and temporal changes of sEH. Villous explant cultures were used to study the effect of HR (8 h at 2% oxygen, followed by 16 h at 8% oxygen, two cycles) on the expression of sEH. Results: Using a mouse monoclonal antibody against human sEH, immunoreactivity of sEH was observed mainly localized in the cytotrophoblasts and, to a lesser extent, the syncytiotrophoblast in the villous tissues throughout gestation. Compared to villous tissues of early gestation, the levels of sEH mRNA and protein were significantly increased in villous samples of mid- and late gestation. Furthermore, villous explants subjected to HR had significantly higher levels of sEH mRNA and protein compared to villous tissues kept at 8% oxygen throughout the experiment. Conclusion: Our results indicate that sEH is likely to play an essential role in the development of human placenta and HR is a possible factor regulating the expression of sEH in the placenta. Keywords: Soluble epoxide hydrolase, Pregnancy, Placenta, Reoxygenation